Consideraciones sobre la historia de la prioridad taxon?mica de oncidium ornithorhynchum - Laura, Mazo C; Gómez Gutiérrez, Alberto; Quintanilla, Sonia R; Bernal, Jaime E; Ortíz Valdivieso, Pedro (Lankesteriana: International Journal on Orchidology, 2014)
The history of the nomenclatural taxonomic priority of the orchid Oncidium ornithorhynchum is yet to be clarified, as successive descriptions and publications of this species were proposed in the eighteenth and nineteenth centuries by botanists such as José Celestino Mutis, John Lindley, Alexander von Humboldt, Aimé Bonpland and Carl S. Kunth, among others. In order to resolve the inconsistencies in taxonomic reports of this species in the course of time, and based on the recent clarification by Jiménez and Hágsater on the type specimen conserved in Paris, we proceeded to review the primary sources associated with its description and botanical nomenclature.